Factors Associated With Neck and Shoulder Pain Complaints In Computer Using Office Stafin Primary Health Center Deli Serdang - Irmayani Irmayani; Rosita Ginting; Anggi Parinduri; Jul Samura; Luci Ginting; Della Sari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
The development of science and technology is increasingly rapid, which is marked by the use of computers in every activity, one of which is office work. Continuous use of a computer while working can cause neck and shoulder pain. This study aims to explain the factors associated with complaints of neck and shoulder pain among computer users. Quantitative with an analytical survey approach using a cross-sectional research design is the focus used in this research. The sample in this study consisted of 31 people using a two-stage cluster random sampling technique. The research was conducted in the Deli Serdang Community Health Center Working Area. Data was collected using primary data using the Nordic Body Map (NBM) questionnaire which was filled in by respondents and the RULA assessment sheet which was filled out by researchers. The results of data collection are processed using statistical software. Data were analyzed using the chi square test with a confidence level of 95% (?=5%). The results of the research show that there is a significant relationship between work posture, intensity of computer use and length of work (p=0.000; 0.012; 0.012) with computer use. It is recommended that office staff who use computers should pay attention to work posture when doing work, using a chair. standards and stretches every 20 minutes after using the computer.